2016
DOI: 10.18585/inabj.v8i2.206
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and Brain-Derived Neurotropic Factor Levels in Ischemic Stroke Subject

Abstract: BACKGROUND: Vascular endothelial growth factor (VEGF) and brain-derived neurotropic factor (BDNF) present during early neuronal development and play important roles in the process of neurorepairing includes angiogenesis, neurogenesis and neuronal plasticity after ischemic stroke. In this study, we observed VEGF and BDNF levels of subjects with ischemic stroke in different onset time.METHODS: A cross sectional study was designed. Study subjects were 51 ischemic stroke subjects, aged 30-80 years old, recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Finally, a total number of 62 articles were entered into our systematic review. We could not enter 16 articles to any meta-analysis group due to the following reasons; providing delta BDNF instead of exact measures (33), reporting BDNF as a proportion to the control group (34), full text was not found, although the abstract was su cient to extract the descriptive data (35), unsatisfactory data and irresponsive author (missing SD) (36), single study group with no comparison or speci c grouping which did not fall into our meta-analysis categorizations (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total number of 62 articles were entered into our systematic review. We could not enter 16 articles to any meta-analysis group due to the following reasons; providing delta BDNF instead of exact measures (33), reporting BDNF as a proportion to the control group (34), full text was not found, although the abstract was su cient to extract the descriptive data (35), unsatisfactory data and irresponsive author (missing SD) (36), single study group with no comparison or speci c grouping which did not fall into our meta-analysis categorizations (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…27 We also collected serum BDNF at day 30 based on another study reported that BDNF level in acute stroke would be increased steadily and reached the highest level after 30 days. 28…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…(36) Long after a stroke occurs, high BDNF plays a crucial role in regeneration and repair by preserving neuronal and plasticity. (37) Rehabilitative treatment impacts BDNF, although changes in BDNF are not consistently linked to enhanced motor performance. Without active rehabilitative treatment, BDNF levels frequently decline.…”
Section: Effects Of Hiit On Neurons In the Cerebral Cortexmentioning
confidence: 99%